Vibrational relaxation of NO(nu=1-3) and NO2(0,0,1) with atmospheric gases - Bohn, B; Doughty, A; Hancock, G; Moore, E; Morrell, C (Royal Society of Chemistry, 1999)
Measurements are reported of the vibrational quenching of NO(v = 1-3) by NO2 and O2, and of NO2(0,0,1) by NO, O2 and N2, close to room temperature. Vibrationally excited NO was formed from the photolysis of NO2 at 308 and 355 nm, and the kinetic behaviour of the different levels was followed by wavelength resolved FTIR emission. The rate constant for the removal of NO(v = 1) by NO2, (1.9 ± 0.2) x 10-12 cm3 molecule-1 s-1, is in excellent agreement with previous measurements. For v = 2 and 3 the rate constants showed a marked increase, with values of (2.9 ± 0.3) and (4.8 ± 0.7) x 10-12 cm3 molecule-1 s-1 respectively, and the relaxation process was found to proceed dominantly through single quantum transitions in NO. However, simultaneous observation of emission from the (0,0,1) level of NO2 revealed that although single quantum exchange between NO and NO2(0,0,1) is close to resonance it took place with less than 50% quantum efficiency. The results are discussed in terms of formation of a N2O3 complex in which free flow of energy is incomplete. For quenching by O2, energy transfer again was found to be dominated by single quantum loss in NO, with rate constants of (2.4 ± 0.2), (5.3 ± 2.6) and (12 ± 4) x 10-14 cm3 molecule-1 s-1 for v = 1, 2 and 3, respectively, in good agreement with previously reported values. Vibrationally excited NO2 was produced by the reaction of NO with NO3, and its quenching kinetics studied by observation of time resolved emission. Rate constants were found to be (4.0-1.5/+1.9) x 10-12, (1.8-0.8/+1.1) x 10-13 and (3.1-1.0/+1.3) x 10-14 cm3 molecule-1 s-1 for quenching by NO, O2 and N2 respectively. The results show that for the first two species the rate constants are similar to those previously reported for quenching of NO2 with moderate but unspecified excitation in the v1 and v3 modes, but for N2 the present value is a factor of four lower. As quenching rate constants for the v1 + v3 modes have been used for estimations of the atmospheric quenching rate of NO2(0,0,1), the present results suggest that these estimates need downward revision by approximately a factor of 2.5.